Hotel accommodation management - Wood, Roy C. (London, United Kingdom : Taylor & Francis, 2018)
This book provides a well-informed and insightful account of hotel accomodation management. The sector is experiencing a wide variety of challenges in the way accommodation services are presented to paying guest, as well as from availability of alternatives to hotels in accommodation provision.
1. Introduction : managing hotel accommodation : an overview -- 2. Trends and issues in hotel ownership and control -- 3. Valuation of hotel assets -- 4. Hotel accomodation design -- 5. Hotel front office management -- 6. Houskeeping and related accommodation services -- 7. Hotel spa and wellness management -- 8. Accommodation and MICE -- 9. Managing accomodation in integratd resorts -- 10. Hotel revenue management -- 11. Hotels and social media -- 12. Hotels and sustainability -- 13. Co-creation and the sharing economy in hospitality and tourism -- 14. Facilities management -- 15. The future(s) of hotel accommodation management
Includes bibliographical references and index.
Keywords: HOTEL MANAGEMENT